Mini furnace project – an educational and green- technopreneurial project / Mohd Azman Yahaya … [et al.] - Yahaya, Mohd Azman; Ismail, Muhammad Hussain; Idris, Nuraisyah; Mohammad Radzi, Muhammad Fazrul (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2018)
This project aims to promote recycling of waste aluminum among school children in Malaysia and to generate income through a program called STEM organized by the Ministry of Education Malaysia. A mini furnace was designed and fabricated according to the design standard for a good and practical furnace. Waste aluminum, in the form of discarded drink cans, are used as the main source of recycling by the furnace. The construction of the furnace commenced with a drawing process using Computer Aided Three-dimensional Interactive Application (CATIA) and ended with a business plan on how to market the furnace to generate income. Besides melting aluminum, the furnace can also be used as a barbeque pot and as a flower pot in order to increase its marketability. With a good marketing strategy and market analysis, the furnace has the potential to generate income. This is a good pilot project especially for university students who are planning in becoming an entrepreneur not only in technological sector but also in environmentally friendly (green) business sector.